Pediatric Intraabdominal Cysts-A Case Series from a Single Tertiary Center Experience - Yazgı Köy; Fikret Dirilenoğlu (AVES Yayincilik, 2024)
Objective: We aimed to analyze the clinical presentation, imaging, histopathology, and surgical management of pediatric intraabdominal cysts, which are relatively common but diverse lesions that pose diagnostic challenges. Materials and Methods: We conducted a retrospective analysis of pediatric intraabdominal cysts from 2010 to 2021 in a single tertiary center. We collected data on demographics, symptoms, radiological findings, surgical approaches, and histopathological diagnoses and compared them with the current literature. Results: A total of 36 cases were included. There were 30 females and 6 males, aged 1 to 16 years. Abdominal pain was the most common symptom, followed by tenderness and distention. Diarrhea and vomiting were also reported in some cases. The cysts varied in size, location, and origin and were diagnosed as lymphangioma, mucinous cystadenoma, paratubal cyst, lowgrade mucinous neoplasm, mature cystic teratoma, duplication cyst, mesothelial cyst, pseudocyst, serous cystadenoma, and simple hepatic cyst. The surgical management depended on the type and location of the cysts and involved excision, oophorectomy, appendectomy, or resection. Conclusion: Pediatric intraabdominal cysts are heterogeneous lesions that require timely diagnosis and surgical resection. They may present with various symptoms and complications, depending on their size and location. Radiological and histopathological evaluation is essential for accurate diagnosis and optimal treatment.